Common image : towards a larger than human communism - Hoelzl, Ingrid (Image, 2021)
Western humanism has established a reifying and predatory relation to the world. While its collateral visual regime, the perspectival image, is still saturating our screens, this relation has reached a dead end. Rather than desperately turning towards transhumanism and geoengineering, we need to readjust our position within community Earth. Facing this predicament, Ingrid Hoelzl and Rémi Marie develop the notion of the common image - understood as a multisensory perception across species; and common ethics - a comportment that transcends species-bound ways of living. Highlighting the notion of the common as opposed to the immune, the authors ultimately advocate otherness as a common ground for a larger than human communism.